Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms. Issue 8 (23rd May 2022) - Pettersen, Amanda K.; Coleman, Melinda A.; Latombe, Guillaume; Gonzalez, Sebastian Vadillo; Williams, Nathan L. R.; Seymour, Justin R.; Campbell, Alexandra H.; Thomas, Torsten; Ferrari, Renata; Stuart‐Smith, Rick D.; Edgar, Graham J.; Steinberg, Peter D.; et al.
Abstract: Aim: Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location: Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period: 2008–2021. Major taxa studied: Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods: Six marine datasets spanning bacteria to fishes were collated for measures of "species" occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results: Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions: Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.